Effects of SARS‑CoV‑2 mRNA vaccines on platelet polyphosphate levels and inflammation: A pilot study. Issue 3 (2022) - UEMATSU, TAKASHI; SATO, ATSUSHI; AIZAWA, HACHIDAI; TSUJINO, TETSUHIRO; WATANABE, TAISUKE; ISOBE, KAZUSHIGE; KAWABATA, HIDEO
No abstract available